O uso de um jogo didático para o ensino do ciclo de vida das plantas - Almeida, Matheus Sidney de (Universidade Federal de São Carlos, 2023)
The development of this monograph is based on the desire to build something meaningful to contribute with a more interesting, motivated, and interactive teaching strategies. In addition, it has as an attribute the production of a product that can be an instrument to face traditional teaching. But this was not by chance, as it was the result of intense reflection on the importance of studying Biology, especially during a material developed for the Diversity and Plant Evolution 1 classes, where the idea of a game about the life cycle of plants was born, which was later improved until arriving at the present proposal. Therefore, this TCC is a research report on the use of the game “Plant Life”. The game was inspired by the card game “Gin Rummy” and includes four groups of plants: Bryophytes, Ferns, Gymnosperms and Angiosperms. Each deck consists of 42 cards, 10 from each plant group and two jokers. The cards form the life cycle of plants: sporophyte, meiosis, spore, germination, gametophyte, female gamete, male gamete, fertilization, zygote, and embryo. The objective of the game is to form the greatest number of life cycles and thus achieve a higher score among the participants. The application was made in a discipline of a Degree in Biological Sciences, in the form of participant observation. The results, which were collected from the students' flexible responses, show that the game provoked motivation, interest, teamwork and was configured as an instrument for reviewing, deepening, thinking, and reflecting on the content, satisfied with the confrontation and combat of plant blindness through education.
Use of a didactic game to teach the life cycle of plant
Keywords: Ciclo de Vida das Plantas; Ensino de Botânica; Jogos Didáticos; Lúdico; Plant Life Cycle; Teaching of Botany; Didactic Games; Ludic; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM::METODOS E TECNICAS DE ENSINO